Survival after cardiac arrest and severe lactic acidosis (pH 6.61) due to haemorrhage. Issue 10 (2nd August 2010) - Spencer, Craig; Butler, John
Abstract : This paper describes a 21-year-old man who presented to the emergency department with a knife wound to his buttock. He had a witnessed cardiac arrest with pulseless electrical activity in hospital as a result of further haemorrhage. His post-resuscitation arterial blood gas revealed a severe lactic acidosis (pH 6.61, lactate 22.0 mmol/l). Despite poor expectations he went on to make a full neurological recovery. To the authors' knowledge, he had the fourth-lowest pH for a cardiac arrest survivor with normal neurology. Severe lactic acidosis occurs post cardiac arrest due to imbalance between cellular oxygen supply and demand. Severe lactic acidosis is associated with hypoxic brain injury but has a low specificity in its prediction. The case illustrates that, especially in younger adults, severe lactic acidosis may be a poor predictor of outcome if it reflects a period of relative hypoperfusion preceding cardiac arrest.